Application of conformal mapping to electrostatic with graphics using mathematica - 494080 Nurul Nadzirah Sidek; Ali Hassan Mohamed Murid; Fakulti Sains (2008)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2008